Adipocytokines in Atherothrombosis: Focus on Platelets and Vascular Smooth Muscle Cells. (2010) - Anfossi, Giovanni; Russo, Isabella; Doronzo, Gabriella; Pomero, Alice; Trovati, Mariella
Abstract : Visceral obesity is a relevant pathological condition closely associated with high risk of atherosclerotic vascular disease including myocardial infarction and stroke. The increased vascular risk is related also to peculiar dysfunction in the endocrine activity of adipose tissue responsible of vascular impairment (including endothelial dysfunction), prothrombotic tendency, and low-grade chronic inflammation. In particular, increased synthesis and release of different cytokines, including interleukins and tumor necrosis factor-α (TNF-α ), and adipokines—such as leptin—have been reported as associated with future cardiovascular events. Since vascular cell dysfunction plays a major role in the atherothrombotic complications in central obesity, this paper aims at focusing, in particular, on the relationship between platelets and vascular smooth muscle cells, and the impaired secretory pattern of adipose tissue.